If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 30 + -10p = 5(2p + -6) Reorder the terms: 30 + -10p = 5(-6 + 2p) 30 + -10p = (-6 * 5 + 2p * 5) 30 + -10p = (-30 + 10p) Solving 30 + -10p = -30 + 10p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-10p' to each side of the equation. 30 + -10p + -10p = -30 + 10p + -10p Combine like terms: -10p + -10p = -20p 30 + -20p = -30 + 10p + -10p Combine like terms: 10p + -10p = 0 30 + -20p = -30 + 0 30 + -20p = -30 Add '-30' to each side of the equation. 30 + -30 + -20p = -30 + -30 Combine like terms: 30 + -30 = 0 0 + -20p = -30 + -30 -20p = -30 + -30 Combine like terms: -30 + -30 = -60 -20p = -60 Divide each side by '-20'. p = 3 Simplifying p = 3
| 5x-3/6=4 | | 48+52=x | | -4x+2(3x-3)=5-9x | | 3(x+4)-7whenx=9 | | 3x+3+2=6x+2-x | | 1.8(2x+3)=3.5(x+2) | | .33(x+2)=.33x+.66 | | b^2-2b-48=0 | | .9z+8.25=1.5(2+2z) | | 100000(1+0.05/4)^360*4 | | 4(x-8)=52-2x | | 12(x-3)=3(2x-1)-1 | | (2x-9)(7x+8)=0 | | 5x-3=8x+7 | | 8(p-.25)=4(2p-.5) | | 25t^2-25=0 | | 0.54+0.12=4 | | 4.8x-3=3.8x | | -1.25x-3.5=13.5 | | t-28=54 | | 2.5(x+2)7.4+13=16 | | -(3x-5)-(2x-6)+1=-5(x+1)-(3x+2)+3 | | 64=6x-x+9 | | 6(x-.33)=2(x+23) | | 5+x+5x=53 | | 2x+10-3x=18 | | 12-2y^2=4 | | y=6-x/3 | | 15+3*3=6y | | 1/4X5 | | 4x^2-5=-1 | | 5x+25=135 |